Semantic Transformation of Public Open Spaces: Republic Square of Bursa - Polat, Sibel; DOSTOĞLU, NESLİHAN (My University, 2017)
Today, urban dilapidation experienced in many city centres related to different reasons affect also public open spaces which become a current issue with discussions about privatisation, disappearance and obsolescence. In this context, public open spaces become an important agenda to revitalize city centres and to rediscover them again in terms of “loss of place identity” issues and efforts “to reinforce place identity”. Thus, the aim of this study is to investigate transformation of public open spaces in terms of identity and urban memory. In this context, the identity of Republic Square located in Bursa city centre was analysed from past to present. Different methods were used to realize this case study, such as archival and literature review, basic observation and deep interviews with 30 users. As a conclusion, it was revealed that environmental aesthetics are still sustained in the square, but spatial experiments and behaviours of users have changed in a negative way due to the power of global capital related to the changing social structure in cities.
Keywords: identity; public open space; public life; meaning; Republic Square; Bursa